Building Of Spirit Of Islamic Entrepreneurship On The Indonesia Young Generation - Wantara, Pribanus; Irawati, S. Anugrahini (Archives of Business Research, 2019)
Since of economic crisis in Indonesia, people tried in various ways to fulfill their needs. Cessation work, limited job opportunities also contribute to increasing the number of unemployment in Indonesia. It encourages people to seek alternatives to improve the standard of an unbalanced economy. Majority Indonesian is Muslim. Hence, it becomes a task to be able to give birth to the entrepreneur Muslim reliable. This article talked about general basic principle of entrepreneurship viewed by history of Muhammad's life as a succeed entrepreneur. Mohammed before being known as prophet, has been recorded as an entrepreneur. Personal success is personal to identify, optimize potency, identity continuously with full confidence andstrong self confidence. So that, it is necessary to refresh the mindset of the basic concepts of business right through entrepreneurship characterized by reviewing the success of Muhammad as the best real entrepreneurship. Learning back of the concept is expected to arouse the public in carrying out efforts to correct and bring benediction Indonesian people, especially in the face of global competition. The results of this study indicate that the basic concept of entrepreneurship according to Muhammad’s life history is built by Integrity, Loyalty, Professionalism and Spirituality.